Challenges Faced by Distance Learners in Pursuance of Literacy Activities at Allama Iqbal Open University - syeda Ghulam Zahra (IJLTP, 2024)
Distance learners need both information literacy and scientific literacy to learn and acquire skills. As they belong from remote areas and their success is conditioned with certain challenges and factors to pursue their literacy skills. There is ample literature indicating the need to address this issue. This paper identifies challenges faced by distance learners in the pursuit of literacy activities at Allama Iqbal Open University. The population of the study comprised all the students of Allama Iqbal Open University from Upper Chitral District. Out of which 100 students were taken as sample using simple random sampling technique. The study was descriptive in nature and participants were administered a questionnaire through survey. The instrument used in this study was validated and reliability was also determined through test-retest reliability. Results indicated challenges regarding access of literacy activities on Aaghi LMS, and challenges regarding teaching and learning. Based on results this paper recommended that suitable plan of action may be devised to address the challenges of distance learners to maximize their literacy activities.